Upaya Pengaktifan Kembali Bank Sampah Dengan Perbaikan Sistem Administrasi Melalui Program KKN Di Desa Margoyoso - Muhamad Arief Afandy; Ryan Yahya Riyanto; Ridwan Nur Fadli; Boy Arya Sadewa; Shakila Ravani; Erlinda Kurnia Rahman; Fermilia Apriyanti; Azhizah Cahya Pamungkas; Ibrahim Movitch; Melati Lintang Kirana; Sri Hastuti (PT. Hasba Edukasi Mandiri, 2025)
Waste management at the village level remains a significant challenge, particularly in Margoyoso Village, Salaman District, Magelang Regency. The previously established waste bank has become stagnant and inactive due to weak administrative systems, low community participation, and a lack of proper waste storage facilities. The Community Service Program (KKN) of Universitas Tidar, in collaboration with the Margoyoso Village PKK Mobilization Team, initiated efforts to revitalize the waste bank by developing administrative record books aimed at improving the documentation system and institutional governance of the waste bank. The implementation method used was a participatory approach through coordination, field observation, and the development and printing of seven types of administrative books, including: Meeting Minutes Book, Guest Book, Cash Book, Customer Waste Deposit Book, Member Register Book, Waste Sales Book, and Savings Master Book. A total of 294 books were distributed to the neighborhood (RT), hamlet, and village levels to support the reactivation of previously dormant waste bank activities. As a result, the waste bank institution began to show improvements in documentation, transparency, and operational readiness. This initiative serves as a foundation for strengthening community-based waste management in a sustainable manner.